Foreign sports research models: comparative analysis - Dolmatova, T. V.; Zubkova, A. V.; Selezneva, E. A.; Kuznetsova, E. V.; Baryaev, A. A. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to analyze the best institutional models of the sports research systems facilitating success of the global sports leading nations.